Biodegradable biomatrices and bridging the injured spinal cord: the corticospinal tract as a proof of principle - Joosten, Elbert A. J. (Springer-Verlag, 2012)
Important advances in the development of smart biodegradable implants for axonal regeneration after spinal cord injury have recently been reported. These advances are evaluated in this review with special emphasis on the regeneration of the corticospinal tract. The corticospinal tract is often considered the ultimate challenge in demonstrating whether a repair strategy has been successful in the regeneration of the injured mammalian spinal cord. The extensive know-how of factors and cells involved in the development of the corticospinal tract, and the advances made in material science and tissue engineering technology, have provided the foundations for the optimization of the biomatrices needed for repair. Based on the findings summarized in this review, the future development of smart biodegradable bridges for CST regrowth and regeneration in the injured spinal cord is discussed.